Construction and Validation of a Chloroplast Expression Vector for the Production of Recombinant Proteins in Chlorella vulgaris - Bolaños-Martínez, Omayra C.; Malla, Ashwini; Rosales-Mendoza, Sergio; Vimolmangkang, Sornkanok (Frontiers in Marine Science, 2022)
Microalgae constitute a diverse group of photosynthetic unicellular microorganisms that have gained immense attention for biotechnological applications. They are promising platforms for the production of high value metabolites and biopharmaceuticals for commercial and therapeutic applications because of their physiological properties and capability to grow easily in both natural and artificial environments. Although the proof of concept for some applications have been achieved for model species, such as Chlamydomonas reinhardtii, genetic engineering methods for microalgae are still in the infancy, thus an expansion of this field is required. The objective of this research was to establish a chloroplast transformation method for the freshwater green algae species Chlorella vulgaris based in a specific expression vector (pCMCC) constructed with endogenous recombination regions, namely 16S–trn I (left) and trn A–23S (right), and the Prrn promoter. Human basic fibroblast growth factor (bFGF) was adopted as a target biopharmaceutical to establish the chloroplast expression approach. The plasmid pCMCC:bFGF was transformed into C. vulgaris via.,electroporation using simple carbohydrate buffers that aid in the transfer of the transgene into the chloroplast genome. Cells transformed with the bFGF gene were selected using kanamycin, and resistant colonies were analyzed by PCR and Western blotting to prove the presence of the transgene and the recombinant bFGF, respectively. bFGF was accumulated in the obtained transplastomic C. vulgaris clones in the range of 0.26 ng/g to 1.42 ng/g as revealed by ELISA-based quantification. Therefore, the designed expression vector in combination with an optimized electroporation protocol constitute a viable approach to successfully develop transplastomic C. vulgaris clones for the low-cost production of biopharmaceuticals. This study paves the way for the chloroplast-based expression in green microalgae as an economical platform for the production of therapeutic proteins and metabolites.